Akupunktur, Regeneration und kardiale Regulation nach Ausbelastung - Niederer, D.; Gonzalez-Rivera, J.; Vogt, L.; Thiel, C.; Hübscher, M.; Rosenhagen, A.; Banzer, W. (Herzfrequenzvariabilität: Gesundheitsförderung - Trainingssteuerung - Biofeedback. Internationales Symposium am 29. und 30. Oktober., 2011)
Background: The physiology of exercise regeneration and interventions to improve post-exercise recovery are significant fields of study in Sports Medicine. First findings indicate an effect of acupuncture on the physiological and mental state in the post-competition period (Akimoto et al., 2003). The current study assessed the immediate effects of needle acupuncture on heart rate variability (HRV) during post-exercise recovery.